Toll-like receptor 2 ligands promote microglial cell death by inducing autophagy - Arroyo, Daniela Soledad (2012)
Microglial cells are phagocytes in the central nervous system (CNS) and become activated in pathological conditions, resulting in microgliosis, manifested by increased cell numbers and inflammation in the affected regions. Thus, controlling microgliosis is important to prevent pathological damage to the brain. Here, we evaluated the contribution of Toll-like receptor 2 (TLR2) to microglial survival. We observed that activation of microglial cells with peptidoglycan (PGN) from Staphylococcus aureus and other TLR2 ligands results in cell activation followed by the induction of autophagy and autophagy-dependent cell death. In C57BL/6J mice, intracerebral injection of PGN increased the autophagy of microglial cells and reduced the microglial/macrophage cell number in brain parenchyma. Our results demonstrate a novel role of TLRs in the regulation of microglial cell activation and survival, which are important for the control of microgliosis and associated inflammatory responses in the CNS.